The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/nl0509069
|View full text |Cite
|
Sign up to set email alerts
|

Basis and Lattice Polarization Mechanisms for Light Transmission through Nanohole Arrays in a Metal Film

Abstract: The extraordinary light transmission through double-hole and elliptical nanohole arrays in a thin gold film is investigated for different orientations of the holes relative to the lattice. Even though these bases have similar symmetry characteristics, the polarization follows the orientation of the basis for the ellipse but remains fixed along a lattice vector for the double holes. Furthermore, the maximum transmitted intensity for linearly polarized light is constant for the ellipse, but decreases for the dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…Transmission enhancement was observed at the fundamental SP 1.50 [±1, 0] THz mode for perpendicular orientation, and 1.85 [0, ±1] THz for parallel orientation occurred at the metallic Si-air interface [27]. The orientation-dependent transmission property is consistent with previous work reported in the both visible and terahertz regions [27,61]. In addition, a transmission minimum occurs in the spectra at 1.95 THz due to the Wood's anomaly [16,27,55].…”
Section: Transition Of a Sp Resonance From A Photonic Crystal Effectsupporting
confidence: 90%
“…Transmission enhancement was observed at the fundamental SP 1.50 [±1, 0] THz mode for perpendicular orientation, and 1.85 [0, ±1] THz for parallel orientation occurred at the metallic Si-air interface [27]. The orientation-dependent transmission property is consistent with previous work reported in the both visible and terahertz regions [27,61]. In addition, a transmission minimum occurs in the spectra at 1.95 THz due to the Wood's anomaly [16,27,55].…”
Section: Transition Of a Sp Resonance From A Photonic Crystal Effectsupporting
confidence: 90%
“…In particular, we used the double nanohole (DNH), which we studied since 2004 [12][13][14] because it creates a local hot-spot of around 10 nm in size in the electric field that interacts more strongly with the nanoparticle of interest.…”
Section: Double Nanohole Optical Tweezersmentioning
confidence: 99%
“…As a result, the orientation of the hole-shape with respect to the lattice plays a role in determining the relative excitation of each resonance [92,101,102]. Recent NSOM studies have confirmed the result that elliptical holes scatter predominantly into TM surface waves perpendicular to the major axis [51].…”
Section: Hole-shape: Basis Effectsmentioning
confidence: 99%